The relations between graduate programs in economics in Brazil: A structural equivalence analysis - Andrea Cabello (EconomiA, 2018)
We analyze the educational background of Economics Professors in Brazilian Economics Graduate Programs, in terms of PhD affiliations. Using a method of structural equivalence, we propose three groups among institutions that granted PhD degrees to Brazilian Economics Professors.
Keywords: B20; 330; Economics Departments; PhD affiliation; Structural equivalence